Evaluation of Treatment Outcomes for Chryseobacterium indologenes Bacteremia developed during Broad-spectrum Antimicrobial Therapy. (4th October 2017) - Moon, Chisook; Lee, Sunwook; Park, Younhee; Shin, Jeong-Hwan
Abstract: Background: Chryseobacterium indologenes is an uncommon human pathogen, but the incidence of bacteremia has been increasing with use of broad-spectrum antimicrobial agents. We investigated clinical characteristics and treatment outcomes for C. indologenes bacteremia. Methods: Patients with C. indologenes bacteremia during the period January 2006 to October 2016 were identified from a computerized database of one tertiary care hospital in South Korea. The medical records of these patients were retrospectively reviewed. Results: A total of 22 episodes of C. indologenes bacteremia were identified. Among them, 21 (95.5%) were hospital-acquired and 17 (77.3%) occurred in patients who were admitted to the intensive care unit. The most frequent route of bacteremia was catheter-related bloodstream infection (13 patients, 59.1%), followed by pulmonary infection (7, 31.8%). Thirteen patients (59.1%) were exposed to carbapenems or colistin in 28 days prior to the culture date of C. indologenes. Antimicrobial susceptibility testing of the 22 isolates showed that minocycline was the most active agent (susceptibility rate: 95.5%), followed by trimethoprim-sulfamethoxazole (86.4%) and ciprofloxacin (50.0%). All isolates were resistant to carbapenems and 12 (54.5%) were only susceptible to TMP-SMX or minocycline. The 28-day mortality and bacteremia-related mortality rate were 45.5% and 40.9%, respectively. Underlying diabetes mellitus ( P = 0.025), inappropriate antimicrobial therapy ( P = 0.015), and an elevated APACHE II score ( P = 0.038) were significantly associated with bacteremia-related mortality. Conclusion: TMP-SMX and minocycline were reliable antimicrobial agents to C. indologenes. Inappropriate antimicrobial therapy was significantly associated with adverse outcome in patients with C. indologenes bacteremia. Antimicrobial stewardship interventions are needed to minimize the exposure of broad-spectrum agents in high-risk patients. Disclosures: All authors: No reported disclosures.